2020
DOI: 10.1007/s00402-020-03647-5
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of concomitant chondral/osteochondral lesions in acute ankle fractures and their effect on clinical outcome: a systematic review and meta-analysis

Abstract: Introduction Despite successful osteosynthesis, some patients report residual symptoms after ankle fractures. One of the reasons behind the postoperative complaints might be traumatic concomitant chondral lesions (CL) and/or osteochondral lesions (OCL) within the ankle joint. The study aims to systematically review the incidence of CL and/or OCL in ankle fractures and to assess their effect on the clinical outcome. Materials and methods This work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…8 While other scholars also reported that the peak of swelling occurred 1-3 days after the operation of periarticular ankle fracture, and the swelling of the affected part would produce negative impacts on the speed of wound healing and local blood circulation of the skin, reducing the effect of fracture healing, and lowing the quality of life of patients. 9 Treatment of patients with a periarticular ankle fracture…”
Section: Discussionmentioning
confidence: 99%
“…8 While other scholars also reported that the peak of swelling occurred 1-3 days after the operation of periarticular ankle fracture, and the swelling of the affected part would produce negative impacts on the speed of wound healing and local blood circulation of the skin, reducing the effect of fracture healing, and lowing the quality of life of patients. 9 Treatment of patients with a periarticular ankle fracture…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular disorders such as ligament disruptions or chondral lesions could be identified and treated in ankle fractures with arthroscopy [ 6 ]. According to a meta-analysis, chondral or osteochondral injuries were found in 65% of patients with ankle fractures [ 7 ]. For this reason, arthroscopically assisted reduction and internal fixation (ARIF) were proposed to treat ankle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of CLs in acute ankle fractures in the literature shows a very broad range of discrepancy. A somewhat more accurate estimation of this incidence was described in a meta-analysis by Darwich et al [14], where a mean value of 58 ± 25% (17-100) was observed, based on 19 included studies [1,[9][10][11][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The incidence, however, varies widely according to the diagnostic method.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence, however, varies widely according to the diagnostic method. In the same meta-analysis [14], the mean incidence was 65 ± 21% in the 16 studies [1,10,11,15,16,[18][19][20][21][22][24][25][26][27][28][29] where arthroscopy was used as diagnostic method and decreased to 19 ± 5% (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) in the only two available studies [9,17] where magnetic resonance imaging (MRI) was the diagnostic tool. The first MRI-based study [17] included 21 prospectively examined patients and reported an incidence of CL of 33%.…”
Section: Introductionmentioning
confidence: 99%